Cruising for Burgers: om kød og kødelighed i Frank Zappas Uncle Meat - Knakkergaard, Martin (Academic Quarter | Akademisk kvarter, 2010)
Martin Knakkergaard Cruising for Burgers – om kød og kødelighed i Frank Zappas Uncle Meat. (Cruising for burgers About flesh and corporeality in Frank Zappa's Uncle Meat). Frank Zappa's concept album and film script Uncle Meat from 1969 can be regarded as a key to his art, his view of society and his understanding of existence. In its concrete material Uncle Meat appears both textually and musically as a close pastiche put kaleidoscopically together from unique samples of especially rock, jazz, musique concrète, pop, electronic, and neoclassic, which in unison with lyrics based on a somewhat absurd imagery depict human alienation, debasement and reification. The article is an account of the universe of Uncle Meat consisting of descriptive analyses of a selection of the key and main elements of the work in order to uncover connections and collisions in music, lyrics and ideology. At the same time it is a deliberation of the relevance of Zappa's total oeuvre as prophetic dystopia.